2010
DOI: 10.1016/j.jcrs.2010.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Surgically induced corneal necrotizing keratitis following LASIK in a patient with inflammatory bowel disease

Abstract: We describe a case of necrotizing keratitis that developed after laser in situ keratomileusis (LASIK) in a 50-year-old woman with inflammatory bowel disease. The patient had not disclosed her history of a total colectomy for recurrent ulcerative colitis and developed bilateral stromal inflammation and corneal melting along the flap edge with ulceration within 3 days of uneventful bilateral LASIK for myopia. She was aggressively managed with topical and systemic corticosteroid therapy. Flap infiltrates graduall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…The degree and extent of keratocyte apoptosis also varies with the type of overlying epithelial injury, and can be influenced by the surgical technique and drugs. [121314151617181920212223242526272829303132333435363738394041424344454647] Therefore, rapid re-epithelialization of the cornea would likely promote wound healing of the underlying stroma with minimal cell apoptosis. [38] Furthermore, the identification of factors that aid re-epithelialization after corneal epithelial injury and prevent complications related to delayed cicatrization, such as scar or haze formation, would optimize surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The degree and extent of keratocyte apoptosis also varies with the type of overlying epithelial injury, and can be influenced by the surgical technique and drugs. [121314151617181920212223242526272829303132333435363738394041424344454647] Therefore, rapid re-epithelialization of the cornea would likely promote wound healing of the underlying stroma with minimal cell apoptosis. [38] Furthermore, the identification of factors that aid re-epithelialization after corneal epithelial injury and prevent complications related to delayed cicatrization, such as scar or haze formation, would optimize surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, sterile peripheral infiltrates after LASIK have been reported, 1-8 including 1 case of necrotizing peripheral infiltrates after LASIK in a patient with inflammatory bowel disease. 8 These cases have been reported with the use of a microkeratome and a femtosecond laser (Intralase, Abbott Medical Optics, Inc.).…”
mentioning
confidence: 99%
“…Lahners et al 8 reported on a patient with known rheumatoid arthritis, who developed bilateral infiltrates after LASIK to the right eye only, demonstrating that surgery in just one eye can trigger an immune reaction in both eyes. Carp et al 10 described a case of necrotizing keratitis that developed after LASIK in a patient with inflammatory bowel disease. The potential initiating events for an immunologic reaction include the deposition of immune complexes, serum autoantibodies, vasculitic injury, aberrant expression of HLA-II antigens on corneal epithelium and keratocytes, or an aberrant cellmediated response to corneal injury.…”
Section: Discussionmentioning
confidence: 99%